Workplace response to HIV/AIDS and the effect of HIV/AIDS on the carriers and occupations of the infected urban population - Bateesa, Carole Sekimpi (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. HIV/AIDS Management))--University of Stellenbosch, 2009.